Exploring piperazine for intrinsic weather-proof, robust and self-healable poly(urethane urea) toward surface and tire protection. (16th June 2021) - Li, Wenjuan; Liu, Xingjiang; Sun, Ailing; Wei, Liuhe; Li, Rui; He, Hangyu; Yang, Shaoli; Wang, Shizhuo; Niu, Yanfen; Li, Yuhan
Abstract: Herein, we report a weather-proof, robust and self-healable poly(urethane urea) elastomer via exploring piperazine (PPA) as chain extender. The amidated PPA moiety enables it to maintain high-level transparency and mechanical properties upon heat and xenon aging for 16 days. Deliberate design of short and long hard segment is implemented by using isophorone diisocyanate (IPDI) and PPA as chain extenders. The long hard segments containing strong urea hydrogen bonds play a crucial role in generating strain-induced crystallization (SIC), resulting in outstanding robustness. The reversibility of hydrogen bonds embodies in room-temperature dissociation-reformation of urethane motifs, and transformation of free and regularly hydrogen-bonded urea motifs into irregular bonding above 35 °C. This elastomer exhibits exceptional comprehensive performances in tensile strength (38.5 ± 1.3 MPa), toughness (134.6 ± 7.0 MJ/m 3 ), puncture resistance (697.9 mJ), elasticity, self-healability and adhesion, which demonstrates outstanding ambient repair of scratches, anti-puncture and self-sealing performance. Graphical abstract: Image 1 Highlights: Weather-proof, robust and self-healable poly(urethane urea) elastomer. Amidated piperazine moiety contributes to anti-aging feature. Long hard segments contains extraordinary evolution of hydrogen bonding. Excellent as vehicle top-paint protective coating and anti-puncture tire sealant.